Structural Insight into the In Vitro Anti-Intravasative Properties of Flavonoids - Julia Eichsteininger; Kerstin Kirisits; Claudia Smöch; Christa Stadlbauer; Chi Huu Nguyen; Walter Jäger; Ali Özmen; Gerhard Ecker; Georg Krupitza; Liselotte Krenn (MDPI AG, 2019)
We investigated the effect of 21 flavonoids in a three-dimensional in vitro system for their ability to inhibit gap formation by MCF-7 breast cancer spheroids in monolayers of lymphendothelial cells. Different representatives of the classes of flavones, flavonols, and flavanones were tested in the circular chemorepellent-induced defects (CCID)-assay. Bay11-7082, a known inhibitor of CCID formation served as the positive control. This study provides the first comparison of the potential of flavonoids to suppress features influencing the intravasation of MCF-7 breast cancer cells aggregates through the lymph endothelial barrier. The most significant effects were seen after incubation with the flavones luteolin, chrysin, and apigenin. Additional hydroxylation or methoxylation in positions 6 or 8, as expected, resulted in decreased activity. The tested flavanones remained without or low efficacy.